2010
DOI: 10.1673/031.010.14113
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Fragment Length Polymorphism Mapping of Quantitative Trait Loci for Economically Important Traits in the Silkworm,Bombyx mori

Abstract: Cocoon related characteristics are economically important traits in the silkworm, Bombyx mori L. (Lepidoptera: Bombycidae). In this study a genetic linkage map was developed that identified QTL controlling the cocoon weight, cocoon shell weight, and cocoon shell percentage using 161 amplified fragment length polymorphism (AFLP) markers. Twenty PstI/TaqI primer combinations were employed to genotype 78 F2 progenies derived from a cross between P107 Japanese inbred line and Khorasan Lemon Iranian native strain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…However, only 58.75% phenotypic variance was explained by the mapping result, which is less than in some previous studies, such as 59.16% and 73.69% found in the research of Mirhoseini et al . () and Zhang et al . () respectively (Table S3).…”
Section: Discussionmentioning
confidence: 93%
“…However, only 58.75% phenotypic variance was explained by the mapping result, which is less than in some previous studies, such as 59.16% and 73.69% found in the research of Mirhoseini et al . () and Zhang et al . () respectively (Table S3).…”
Section: Discussionmentioning
confidence: 93%
“…The ability to synthesize silk protein, measured by CSW, is a quantitative trait [2]. Several studies have explored the genetic basis of this trait using quantitative trait loci (QTL) mapping [7][8][9][10][11] and selection analysis [12,13]. However, fine mapping and cloning of genes that affect silk protein synthesis has not been done.…”
Section: Introductionmentioning
confidence: 99%
“…Deciphering the genetic basis underlying silkworm improvement may contribute to the identification of the genes controlling silk‐related traits. To date, only several studies have been conducted to explore the genetic basis of these traits via quantitative trait loci mapping (Li et al., 2015; Lu et al., 2004; Mirhoseini et al., 2010; Zhan et al., 2009; Zhang et al., 2010), and no gene has been identified by functional validation. However, genome‐wide research on silkworm improvement has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%